The adoption of performance measures and management accounting system in enhancing managerial performance in Malaysian local government - Badariah Haji Din; Muzafar Shah Habibullah (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
In many organizations, different performance measures were employed to assess different aspects of managers’ performance. Some of the measures were yet to be developed, some developed but only in a very selective way, and some already presented but not adopted or only partly used. At the same time, management accounting systems might have the potential and capability of providing necessary information for planning, decision making and motivating managers’ performance. Hence, this study examined the effect of the adoption of performance measures and management accounting system in enhancing the managers’ performance in Malaysian local government. The data were collected through a questionnaire survey of 131 heads of departments in Malaysian local government. A structural equation modelling technique was utilised to examine the mediating effects of performance measures and management accounting system on the relationship between budgetary participation and managerial performance through a path analysis. The findings showed that the adoption of performance measures and management accounting system had strengthened the relationship between budget participation and managerial performance. The findings pointed to the practical relevance of the performance measures and management accounting system to the current management setting of government organizations.